"Can Magnetic Resonance Enterography (MRE) replace ileo-colonoscopy for evaluating disease activity in Crohn's disease?". (February 2019) - Varyani, Fumi; Samuel, Sunil
Abstract: Crohn's disease is a form of chronic inflammatory bowel disease that can lead to structural bowel damage due to transmural inflammation. Ileo-colonosocopy is currently essential for initial diagnosis. Reassessment of disease burden is frequently needed during episodes of active disease and when evaluating treatment efficacy. This review compares the role of Magnetic Resonance Enterography (MRE) and ileocolonoscopy in Crohn's disease management and whether cross-sectional imaging can replace invasive endoscopic tests. MRE can give information on the small bowel not visible at ileo-colonoscopy, and on extra-luminal complications. Evaluation of the bowel by MRE allows assessment of the submucosa and serosa, and thus transmural healing. MRE offers a well tolerated investigation and additional information on disease activity to better manage patients with Crohn's disease. Increasingly, there are a range of newer techniques such as diffusion weighted imaging, magnetisation transfer and motility MRI which provide greater information on fibrosis and predictors to treatment response which has been lacking despite the use of ileo-colonoscopy for several decades.